2022
DOI: 10.3390/healthcare10071257
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Digital Flipped Learning Evidence-Based Practice on Nurses’ Knowledge, Attitude, and Practice: A Quasi-Experimental Trial

Abstract: Background: Evidence-based care has become critical in raising the quality of medical facilities. The implementation of evidence-based practice helps medical practitioners make better clinical decisions. Objective: The objective of this study was to investigate whether the innovative flipped teaching model could be as effective as the conventional teaching model in terms of knowledge, attitude, and practice and to confirm the continuous effect. Design: A quasi-experimental design using the flipped and conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
3
1
0
Order By: Relevance
“…This finding aligns with a study that showed a statistically significant improvement in nurses’ perceptions of EBP [ 46 ]. Additionally, our study’s results are consistent with those of Chao et al [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding aligns with a study that showed a statistically significant improvement in nurses’ perceptions of EBP [ 46 ]. Additionally, our study’s results are consistent with those of Chao et al [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…enhance healthcare workers' knowledge temporarily. Like the present study, [40][41][42][43]. Moreover, the current study found that nurses who took part in the web-based training program demonstrated improved EBP skills.…”
Section: Plos Onesupporting
confidence: 68%
“…In sum, our study and previous ones ( 3 , 5 , 20 22 ) show that medi-VR simulation and flipped learning can be used as effective interventional education for emergency care for cardiac arrest in the prehospital field. In particular, this study found that the medi-VR simulation method was superior to flipped learning in CPR performance.…”
Section: Discussionsupporting
confidence: 66%
“…Flipped learning-based intervention education among nursing students was effective for knowledge, attitude, and clinical practice immediately after intervention and even one month later compared with a conventional learning method ( 20 ). Moreover, after three months, the knowledge score was even higher, although the attitude score was lower than that in the conventional learning method.…”
Section: Discussionmentioning
confidence: 99%